1994
DOI: 10.2165/00003088-199427060-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pefloxacin Clinical Pharmacokinetics

Abstract: Pefloxacin has a broad spectrum of activity against a great number of Gram-negative and Gram-positive bacteria. It is also capable of penetration into cells, yielding high tissue:serum ratios, with implications for the treatment of infections caused by intracellular pathogens. Pefloxacin is well absorbed from the gastrointestinal tract. Its elimination half-life ranges from 6.2 to 12.4 hours. After repeated administration, a major change in pharmacokinetic parameters is observed. Pharmacokinetic parameters are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…The concentrations of pefloxacin and enoxacin and their derived pharmacokinetic parameters in this study were very similar to those observed in previous multiple‐dose studies with 400 mg twice a day 26 , 27 , 28 . Likewise, caffeine pharmacokinetics without coadministration of a quinolone corresponded to published data 21 .…”
Section: Discussionsupporting
confidence: 87%
“…The concentrations of pefloxacin and enoxacin and their derived pharmacokinetic parameters in this study were very similar to those observed in previous multiple‐dose studies with 400 mg twice a day 26 , 27 , 28 . Likewise, caffeine pharmacokinetics without coadministration of a quinolone corresponded to published data 21 .…”
Section: Discussionsupporting
confidence: 87%
“…A chemical reaction was thought to occur between the chemical species in solution. The impregnated disc for the microbiological evaluation of pefloxacin was therefore based on the amount of pefloxacin effectively present for impregnation (Bressole et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the bioavailability of numerous fluoroquinolones exceeds 90%, evidencing a good overall absorption (4,15,24). In the case of ciprofloxacin, an "absorption window" along the human gastrointestinal tract has been suggested (10).…”
Section: Discussionmentioning
confidence: 99%